Therapy for pneumonitis and sialadenitis by accumulation of CCR2-expressing CD4(+)CD25(+ )regulatory T cells in MRL/lpr mice - Hasegawa, Hitoshi (BioMed Central, 2007)
Adoptive transfer of CD4(+)CD25(+ )regulatory T cells has been shown to have therapeutic effects in animal models of autoimmune diseases. Chemokines play an important role in the development of autoimmune diseases in animal models and humans. The present study was performed to investigate whether the progression of organ-specific autoimmune diseases could be reduced more markedly by accumulating chemokine receptor-expressing CD4(+)CD25(+ )regulatory T cells efficiently in target organs in MRL/MpJ-lpr/lpr (MRL/lpr) mice. CD4(+)CD25(+)Foxp3(+ )T cells (Treg cells) and CD4(+)CD25(+)Foxp3(+ )CCR2-transfected T cells (CCR2-Treg cells) were transferred via retro-orbital injection into 12-week-old MRL/lpr mice at the early stage of pneumonitis and sialadenitis, and the pathological changes were evaluated. Expression of monocyte chemoattractant protein-1 (MCP-1)/CCL2 was observed in the lung and submandibular gland of the mice and increased age-dependently. The level of CCR2 expression and MCP-1 chemotactic activity of CCR2-Treg cells were much higher than those of Treg cells. MRL/lpr mice to which CCR2-Treg cells had been transferred showed significantly reduced progression of pneumonitis and sialadenitis in comparison with MRL/lpr mice that had received Treg cells. This was due to more pronounced migration of CCR2-Treg cells and their localization for a longer time in MCP-1-expressing lung and submandibular gland, resulting in stronger suppressive activity. We prepared chemokine receptor-expressing Treg cells and demonstrated their ability to ameliorate disease progression by accumulating in target organs. This method may provide a new therapeutic approach for organ-specific autoimmune diseases in which the target antigens remain undefined.